STRATEGIES TO IMPROVE THE QUALITY OF VISITATION SERVICES IN CLASS IIB GUNUNGSITOLI PRISON - S. N., Erwin Romi; Rifani, Denny Nazaria (Universitas Nusa Cendana, 2025)
This article discusses the strategy for improving the quality of visiting services at the Gunungsitoli Class IIB Correctional Institution. Visiting services are the right of prisoners, but in fulfilling them, there are still things that make people less satisfied, such as officer behavior, infrastructure, long service times, and procedures that are not yet understood. This research uses a qualitative method with a case study approach, where data is collected through interviews, observation, and documentation. This research uses the NVIVO 14 tool, which involves data, data processing, use of search commands, frequency calculations, and further analysis. The analysis was conducted using service quality improvement strategies, namely structure development strategies, development strategies and simplification of procedure systems, infrastructure development strategies, culture and culture development strategies, and entrepreneurship development strategies. The results of the study indicate that it is necessary to develop in the visiting service section both infrastructure, such as chairs and technological tools; creativity and service innovation; the behavior or attitude of officers in providing services; simplifying the procedure system; and training that should be followed by officers to improve the services provided because then service delivery will be better and more developed. Keywords: Visiting Service; Behavior; Infrastructure; Long Service Times; Procedures